Pemalsuan Identitas sebagai Alasan Pembatalan Perkawinan: Tinjauan Kritis Putusan Pengadilan Agama Lubuk Pakam Nomor 2506/Pdt.G/2025/PA.Lpk - Zaini Munawir; Pagar Pagar; Ramadhan Syahmedi (Mahesa Research Center, 2026)
Identity falsification in marriage constitutes a serious legal issue that affects the validity of the marriage contract and the protection of the parties’ rights. This study aims to analyze the legal basis for marriage annulment due to identity falsification and the judicial considerations in the Decision of the Lubuk Pakam Religious Court Number 2506/Pdt.G/2025/PA.Lpk from the perspectives of positive law and Islamic law. This research employs normative legal research using statutory and case approaches. The findings indicate that identity falsification, particularly concerning prior marital status, represents a substantive violation that results in a defect of consent in the marriage contract. The panel of judges grounded the annulment on Article 22 of Law Number 1 of 1974 on Marriage and Article 72 paragraph (2) of the Compilation of Islamic Law, while also emphasizing the principles of honesty and free consent in Islamic law. The study concludes that the decision is normatively consistent with applicable legal provisions; however, it highlights the need to strengthen substantive justice and preventive measures to deter future practices of identity falsification in marriage